Adhesive properties of Vibrio cholerae: nature of the interaction with intact mucosal surfaces. - Freter, R (1976)
Two companion papers in this series have characterized the interaction between Vibrio cholerae and the surfaces of eukaryotic cells. The present paper reports studies of the association between vibrios or Salmonella enteritidis and intact slices of intestinal tissue. A significant number of differences were noted in the characteristics of bacterial adhesion in these systems. The results are interpreted to indicate the presence of at least two receptors for vibrio adhesion on the mucosal surface of the rabbit small intestine. The receptor mediating the adhesion of salmonella appeared to be distinct from these. A primary role for bacterial motility in the process of adhesion of vibrios to mucosal surfaces could not be demonstrated in the assay systems studied. Rather, loss of motility in mutant vibrios appeared to be correlated with the simultaneous loss of adhesive factors (adhesins) from the bacterial surface. The inhibition of vibrio adhesion to slices of intestinal tissues by antibody to the heat-stable antigens of V. cholerae occurred in the absence of bacterial agglutination. Agglutination in this assay system appeared to be an artifact in that it could be observed only in experiments where extremely high concentrations of vibrios were used. We speculate that such high vibrio concentrations are not likely to be present in humans at the time of infection and that agglutination in the lumen of the intestine might therefore play only a minor role in prophylactic immunity against natural cholera and other enteric infections of humans.